Perlindungan Hukum Terhadap Anak sebagai Pelaku Tindak Pidana Pengeroyokan yang Melibatkan Perguruan Silat (Studi Putusan Pengadilan Negeri No. 11/Pid.Sus-Anak/2023/PN Mjk) - M. Abdul Hasyim; Nur Handayani; M. Syahrul Borman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to explore legal protection for children as perpetrators of gang violence, with a special focus on cases involving martial arts schools. Gang violence involving children and martial arts schools often poses complex challenges in terms of law and child protection. The research methods used are normative and empirical legal research. The type of research used by the author is normative or doctrinal legal research. The data in this study were obtained through library research so that the research data came from secondary data, namely District Court Decision No. 11 / Pid.Sus-Anak / 2023 / PN Mjk). The results of the study indicate that the application of criminal law based on District Court Decision No. 11 / Pid.Sus-Anak / 2023 / PN Mjk) relating to formal criminal law and material criminal law is appropriate, because the procedural procedures and the application of articles in the decision are in accordance with the Criminal Procedure Code, the Juvenile Criminal Justice System Law, and the Child Protection Law. Then, related to legal protection for children, the fulfillment of children's rights has not been implemented optimally.